The Relationship Between Knowledge And Caregiver Attitudes Towards Palliative Care At Melania Pedemangan Nursing Home - Kristoforus Marselinus; Yurita Mailintina; Ribka Sabarina Panjaitan; Ika Mustafida; Ria Efkelin (Sean Institute, 2024)
Palliative care is an approach that focuses on improving the quality of life of patients and their families who are facing life-threatening disease-related problems. This treatment involves the prevention and reduction of suffering through early detection, assessment, and management of pain and other physical, psychosocial, and spiritual problems. This type of research is quantitative with a Cross-Sectional design. The research approach used is a quantitative approach, namely the use of questionnaires and survey research techniques which are components of quantitative research. This study evaluates the relationship between knowledge and caregiver attitudes towards palliative care in the Melania Pedemangan nursing home. The results of the analysis showed that there was a positive and significant relationship between knowledge and caregiver attitudes, with a Pearson correlation of 0.537 and a significance value of 0.000. In conclusion, knowledge is effective in improving caregivers' attitudes towards palliative care in the Melania Pedemangan nursing home.